Evaluation of the efficacy and safety of vilazodone for treating major depressive disorder - Zhang, Xiao-Fei (Neuropsychiatr Dis Treat, 2015)
PURPOSE: Vilazodone is a novel serotonin (5-HT)-reuptake inhibitor and 5-HT(1A) partial agonist that was recently developed for the treatment of major depressive disorder (MDD). We conducted a meta-analysis and systematic review to better evaluate the efficacy and safety of vilazodone. MATERIALS AND METHODS: We performed a thorough literature search to identify all randomized double-blind placebo-controlled trials that were designed to investigate the efficacy of vilazodone for the treatment of MDD, and that were published in electronic databases, including Medline, Embase, and the Cochrane Central Register of Controlled Trials. A manual search was also conducted to investigate the relevant references of the retrieved studies. Subsequently, we conducted a meta-analysis and systematic literature review. RESULTS: A total of five randomized controlled trials were finally included, involving 1,200 patients with vilazodone and 1,193 patients with placebo. The primary efficacy end point of the Montgomery–Åsberg Depression Rating Scale (standardized mean difference −3.58, 95% confidence interval −4.59 to −2.56; P<0.00001), and the key secondary efficacy end points (Clinical Global Impression - Severity scale, Clinical Global Impression - Improvement scale, and Hamilton Anxiety Rating Scale) indicated that vilazodone was more effective than placebo. Most common adverse events, including diarrhea and nausea, were evaluated, and safety assessments indicated that vilazodone was well tolerated (diarrhea odds ratio 3.54, 95% confidence interval 2.81–4.45; P<0.00001; nausea odds ratio 3.85, 95% confidence interval 3.00–4.96; P<0.00001; discontinuations due to adverse events odds ratio 2.71, 95% confidence interval 1.81–4.05; P<0.00001). CONCLUSION: Our findings indicate that the novel antidepressant vilazodone is effective and safe for MDD, with a low occurrence of side effects. It offers promise as an effective oral drug for the treatment of MDD, with a balance of efficacy and tolerability.